2017
DOI: 10.1108/jsbed-01-2017-0023
|View full text |Cite
|
Sign up to set email alerts
|

The effect of family business professionalization on dividend payout

Abstract: This paper contributes to our understanding of dividend payout in privately held familycontrolled firms by adopting a family business professionalization perspective. Based on a sample of 492 small to medium-sized family-controlled firms, the results show that professionalized family firms pay higher dividends to their shareholders than less professionalized firms. In particular the use of financial control systems, nonfamily involvement in governance systems, and the use of human resource control systems have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 92 publications
(182 reference statements)
4
27
0
2
Order By: Relevance
“…In addition to that, bibliometric results have shown that financial decision making within family businesses is a growing field of research. That trend was reported by other works (Michiels, & Molly, 2017;Lozano, 2015).…”
Section: General Trendssupporting
confidence: 88%
See 3 more Smart Citations
“…In addition to that, bibliometric results have shown that financial decision making within family businesses is a growing field of research. That trend was reported by other works (Michiels, & Molly, 2017;Lozano, 2015).…”
Section: General Trendssupporting
confidence: 88%
“…By reviewing the literature on the above matter, we conclude that great efforts have been made to explore family businesses and the peculiarities of their financial policies but, these efforts remain insufficient. The findings of this review highlighted that financial choices depend on several factors, both cognitive and emotional and that knowledge on capital structure decisions is still dispersed and inconclusive as reported by (Michiels & Molly, 2017). Additionally, research on investment policy has been limited to the R&D investment and private equity investors while research on dividends policy in family businesses was considerably underestimated.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…For example, using a sample of Belgian small companies, Vandemaele and Vancauteren (2015) show that dividend payout is low when a family CEO runs the business with a family-dominated board. The finding is consistent with the view that socioemotional objectives as well as professionalization of family business, thereby leading to nonfamily involvement in governance systems, are important drivers of dividend policies of private small companies (Michiels et al, 2017). Similarly, Calabrò et al (2020) document that socioemotional factors affect financial reporting quality and earnings management strategies (the choice between accrual versus real earnings management) in Italian private family firms.…”
Section: Introductionsupporting
confidence: 83%